Co-Co LDH-derived CoSe2 anchored on N-doped carbon nanospheres as high-performance anodes for sodium-ion batteries. (10th November 2022) - Lin, Qifeng; Yuan, Zeyu; Wang, Dongyi; Wei, Wei; Wang, Xibin; Han, Wei; Wang, Lili
Highlights: Nitrogen-doped hollow carbon nanospheres prepared by in-situ template method show enhanced sodium storage. The charge-discharge cycle performance and theoretical calculation of NHCNS@CoSe2 @C are adequately studied. NHCNS@CoSe2 @C anode exhibit good capacity retention and rate performance. Abstract: The growing problem of limited lithium resource reserves has resulted in increased attention and a corresponding surge in sodium-ion battery (SIB) research. However, SIBs have disadvantages, such as a short cycle life and low energy density. The lack of high capacity and long-cycle stability anode materials are important factors hindering the development of SIBs. In this study, hollow carbon nanospheres were nitrogen-doped, and the zeolitic imidazolate framework-67 was used as a precursor to synthesize cobalt-based layered double hydroxide using the hydrothermal method followed by synthesizing an NHCNS@CoSe2 @C complex using calcination and carbon coating. In this design concept, the hollow-cavity structure of the carbon nanospheres provided shorter electron diffusion paths and increased stability; the introduction of nitrogen increased the number of defect sites and charge density of the porous carbon materials, which, with the transition metal selenide, enhanced the conductivity of the final product. The resulting carbon-supported anode material, NHCNS@CoSe2 @C, had an initial stable discharge capacity of 465.6 mAh g   −   1 at a current density of 0.1 A g   −   1 and maintained a high capacity of 373.8 mAh g   −   1 after 100 cycles. Moreover, it exhibited a high rate performance of 285.6 mAh g   −   1 at a current density of 5 A g   −   1 . Graphical abstract: Image, graphical abstract